Effect of volatile and total intravenous anesthesia on syndecan-1 shedding after minimally invasive gastrectomy: a randomized trial - Na Young Kim (Nature Portfolio, 2021)
Abstract This study aimed to compare the effects of volatile anesthesia and total intravenous anesthesia (TIVA) on syndecan-1 shedding in patients with gastric cancer undergoing minimally invasive gastrectomy. Patients were randomly assigned to either the Volatile (n = 68) or the TIVA (n = 68) group. Anesthesia was maintained with sevoflurane/remifentanil or propofol/remifentanil in the Volatile and TIVA groups, respectively. Serum syndecan-1 was evaluated at pre-operation, end of operation, and postoperative day (POD) 1. Inflammatory markers including white blood cell (WBC) count, neutrophil-to-lymphocyte ratio (NLR), and C-reactive protein (CRP), were also measured at pre-operation, end of operation, and POD 1, 2, 3, and 5. The TIVA group showed significantly lower levels of syndecan-1 at the end of the operation compared to the Volatile group; however, no difference was seen between the groups at POD 1. The WBC count and NLR were significantly lower in the TIVA group at the end of the operation than the Volatile group, but there were no differences between the groups at POD 1, 2, 3, and 5. CRP levels were similar between the groups at all time points. In conclusion, despite TIVA being superior to volatile anesthesia in protecting endothelial glycocalyx during the operation, both did not prevent postoperative syndecan-1 shedding after gastrectomy. Clinical trial registration number: NCT04183296 (ClinicalTrial.gov, 03/12/2019).